2014
DOI: 10.1007/s12264-013-1449-1
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent blockade by bupivacaine of cardiac sodium channels expressed in Xenopus oocytes

Abstract: Bupivacaine ranks as the most potent and efficient drug among class I local anesthetics, but its high potential for toxic reactions severely limits its clinical use. Although bupivacaine-induced toxicity is mainly caused by substantial blockade of voltage-gated sodium channels (VGSCs), how these hydrophobic molecules interact with the receptor sites to which they bind remains unclear. Na v 1.5 is the dominant isoform of VGSCs expressed in cardiac myocytes, and its dysfunction may be the cause of bupivacainetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Potency values for bupivacaine to block cardiac sodium channels vary widely and are hard to interpret since drug binding depends on resting membrane potential, stimulation rate, and extracellular sodium concentration. 17,18 Since there is an almost linear relation between sodium currents and upstroke velocity, 19 we simultaneously measured action potential and force in intact muscle preparations of guinea pig ventricles exposed to a wide range of bupivacaine concentrations.…”
Section: Clinically Relevant Concentrations Of Bupivacaine Diminish Contractile Force Independent Of Sodium Channel Blockmentioning
confidence: 99%
“…Potency values for bupivacaine to block cardiac sodium channels vary widely and are hard to interpret since drug binding depends on resting membrane potential, stimulation rate, and extracellular sodium concentration. 17,18 Since there is an almost linear relation between sodium currents and upstroke velocity, 19 we simultaneously measured action potential and force in intact muscle preparations of guinea pig ventricles exposed to a wide range of bupivacaine concentrations.…”
Section: Clinically Relevant Concentrations Of Bupivacaine Diminish Contractile Force Independent Of Sodium Channel Blockmentioning
confidence: 99%
“…The differential activity of tafluprost upon both ion channels (as well as its higher potency as compared with the local anesthetic bupivacaine (Stoetzer et al, 2016)) roughly agrees with the theoretical binding energies predicted by the docking simulations. Noteworthy, although tafluprost was clearly less active in NaV1.5 than in TASK-1, it still shows a potency in a similar range as that shown by the well-known sodium channel blocker bupivacaine (Zhang et al, 2014). Even though this is the first time that an activity of tafluprost on cardiac channels is described, it should be noted that it had been reported that the drug is able to induce a relaxation of rabbit ciliary arteries precontracted with a high-potassium solution (Dong et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, both agents induce less use-dependent block compared to bupivacaine and other LAs but showing similar effects to methadone which was reported to have relevant LA-like properties. 28 , 29 , 67 In addition to the use-dependent block as a surrogate for an increasing affinity of Nav1.5 channels towards an agent as a response to repetitive depolarizations, substance-specific kinetics are responsible for the duration of their blocking capabilities. Fast onset of inhibition and slow dissociation from inactivated cardiac Na + channels of bupivacaine and amitriptyline led to the generally used classification of “fast in” and “slow out” blockers.…”
Section: Discussionmentioning
confidence: 99%